2007
DOI: 10.1016/j.str.2007.01.004
|View full text |Cite
|
Sign up to set email alerts
|

How Does a Voltage Sensor Interact with a Lipid Bilayer? Simulations of a Potassium Channel Domain

Abstract: SummaryThe nature of voltage sensing by voltage-activated ion channels is a key problem in membrane protein structural biology. The way in which the voltage-sensor (VS) domain interacts with its membrane environment remains unclear. In particular, the known structures of Kv channels do not readily explain how a positively charged S4 helix is able to stably span a lipid bilayer. Extended (2 × 50 ns) molecular dynamics simulations of the high-resolution structure of the isolated VS domain from the archaebacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
88
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(111 citation statements)
references
References 48 publications
23
88
0
Order By: Relevance
“…Cysteine reactivity measurements first suggested the presence of water vestibules within VSDs (37)(38)(39)(40)(41)(42)(43)(44)(45). X-ray structures (6,20,30) show that bending of S3 away from the VSD core creates deep crevices at the center of the S1-S4 helical bundle that can be penetrated by water.…”
Section: Resultsmentioning
confidence: 99%
“…Cysteine reactivity measurements first suggested the presence of water vestibules within VSDs (37)(38)(39)(40)(41)(42)(43)(44)(45). X-ray structures (6,20,30) show that bending of S3 away from the VSD core creates deep crevices at the center of the S1-S4 helical bundle that can be penetrated by water.…”
Section: Resultsmentioning
confidence: 99%
“…It is thought that the voltage sensor domain move in response to changes in voltage across the membrane bilayer but the exact nature and extent of such motions is still undetermined. It is likely then, that simulations [110][111][112] in combination with experimental data will be able to provide information on the location of the voltage sensor relative to the membrane and a complete structural understanding of the conformational changes during the transition from the closed to the open state in Kv channels.…”
Section: Structural Changes During Ion Channel Gatingmentioning
confidence: 99%
“…Furthermore, it has been postulated that the S4 transmembrane helix in the KvAP K ϩ channel, which contains four arginine side chains, moves within the membrane in response to a transmembrane potential (33,34). Molecular dynamics studies (35,36) have shown that arginine insertion into a bilayer is facilitated by a network of hydrogen bonds with the lipid phosphate groups and water molecules. A common feature of these mechanisms is that the lipid bilayer structure can undergo large perturbations in response to interactions with proteins.…”
mentioning
confidence: 99%